Immobilization of carboxypeptidase from Sulfolobus solfataricus on magnetic nanoparticles improves enzyme stability and functionality in organic media - Sommaruga, Silvia (BioMed Central, 2014)
BACKGROUND: Superparamagnetic iron oxide nanoparticles (MNP) offer several advantages for applications in biomedical and biotechnological research. In particular, MNP-based immobilization of enzymes allows high surface-to-volume ratio, good dispersibility, easy separation of enzymes from the reaction mixture, and reuse by applying an external magnetic field. In a biotechnological perspective, extremophilic enzymes hold great promise as they often can be used under non-conventional harsh conditions, which may result in substrate transformations that are not achievable with normal enzymes. This prompted us to investigate the effect of MNP bioconjugation on the catalytic properties of a thermostable carboxypeptidase from the hyperthermophilic archaeon Sulfolobus solfataricus (CPSso), which exhibits catalytic properties that are useful in synthetic processes. RESULTS: CPSso was immobilized onto silica-coated iron oxide nanoparticles via NiNTA-His tag site-directed conjugation. Following the immobilization, CPSso acquired distinctly higher long-term stability at room temperature compared to the free native enzyme, which, in contrast, underwent extensive inactivation after 72 h incubation, thus suggesting a potential utilization of this enzyme under low energy consumption. Moreover, CPSso conjugation also resulted in a significantly higher stability in organic solvents at 40°C, which made it possible to synthesize N-blocked amino acids in remarkably higher yields compared to those of free enzyme. CONCLUSIONS: The nanobioconjugate of CPSso immobilized on silica-coated magnetic nanoparticles exhibited enhanced stability in aqueous media at room temperature as well as in different organic solvents. The improved stability in ethanol paves the way to possible applications of immobilized CPSso, in particular as a biocatalyst for the synthesis of N-blocked amino acids. Another potential application might be amino acid racemate resolution, a critical and expensive step in chemical synthesis.